The Concept of Love and The Basis of Its Doctrines Between Maqamat and Haal - Abdul Wachid Bambang Suharto (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2021)
Basically, Sufism is the spiritual